Austria : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper presents a comparison on public expenditure of Austria and other countries. In the past decade, Austria's government expenditure growth has been very steady, thus avoiding the boom-bust pattern of some other European countries. However, expenditure levels are relatively high, and the difference with Germany has been widening. Compared with other countries, spending is particularly high for pensions, capital transfers and subsidies, including in the transport sector. According to economic classification, the composition of expenditure in the main categories has been more stable. Social benefits and transfers in kind, increasing by 0.7 percentage points between 2002 and 2012, have remained the highest component by far. Nevertheless, expenditure levels in Austria are relatively high, and the difference with Germany has been widening. A cross-country analysis of public spending by different type of categories shows several areas where spending stands out.